Fomo, Filter, dan AI dalam Pembentukan Citra Bisnis - Indri Kharisma; Indah Ayu Ningtyas; Arif Nur Hidayat; Raden Wahyu Utomo Martianto (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
This study analyzes the relationship between Fear of Missing Out (FOMO), the use of digital filters, and artificial intelligence(AI) technology in shaping business image in the digital era. The phenomenon of FOMO has become a major driving forcebehind business engagement in following aesthetic trends to maintain relevance on social media platforms. Using aquantitative approach with an explanatory research design, this study examines the effect of FOMO on the intensity ofdigital filter and AI usage and its impact on business image. Data were collected through an online survey using a Likertscaleinstrument and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM).The findings indicatethat FOMO has a significant influence on the use of digital filters and AI technologies and exerts both direct and indirecteffects on business image. The application of visual technologies is shown to enhance perceptions of professionalism,aesthetic appeal, and brand credibility among consumers. Furthermore, the study reveals that psychological pressure anddigital social dynamics accelerate the frequency of visual content updates by businesses. These results contributetheoretically to the integration of psychological variables and visual technologies in the formation of digital brand image,while also offering practical implications for business practitioners in designing ethical, adaptive, and effective visualcommunication strategies. The study emphasizes the importance of balancing AI-based digital aesthetics with brandauthenticity to create a strong and sustainable business image amid increasingly intense visual competition